2022
DOI: 10.1167/iovs.63.6.2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Pigment Particles in Aqueous Drainage Structures in a DBA/2J Mouse Model of Pigmentary Glaucoma

Abstract: Purpose To characterize the distribution of pigment particles in aqueous drainage structures of DBA/2J mice with different intraocular pressure (IOP) levels. Methods DBA/2J mice were monitored from 9 to 44 weeks of age. IOP measurements were performed periodically. At 12, 20, 28, and 36 weeks, three mice were randomly selected for each time point and divided into three IOP groups. The morphology, size, and quantity of pigment particles in aqueous drainage structures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…15 We chose 3, 6, and 9 months as the main time points to observe the effect of varying degrees of pigment dispersion on ocular immune privilege in DBA2J mice according to our previous studies. 29 In our present study, we observed elevated levels of AH protein and serum protein, accompanied by an increase in the number of immune cells in the anterior chamber. These findings indicate the disruption of the blood–aqueous barrier and the occurrence of inflammation in eyes affected by pigment dispersion.…”
Section: Discussionsupporting
confidence: 64%
“…15 We chose 3, 6, and 9 months as the main time points to observe the effect of varying degrees of pigment dispersion on ocular immune privilege in DBA2J mice according to our previous studies. 29 In our present study, we observed elevated levels of AH protein and serum protein, accompanied by an increase in the number of immune cells in the anterior chamber. These findings indicate the disruption of the blood–aqueous barrier and the occurrence of inflammation in eyes affected by pigment dispersion.…”
Section: Discussionsupporting
confidence: 64%
“…It is characterized by optic atrophy and visual field defects. Elevated IOP and RGC damage are generally considered to be the main causes of glaucoma [41] . In our study, the DBA/2J mouse model with elevated IOP showed some typical features of glaucoma [42] .…”
Section: Acteoside Relieves Cell Injury In Glutamate-induced Rgc5 Cel...mentioning
confidence: 99%